1988
DOI: 10.1017/s0266467400002686
|View full text |Cite
|
Sign up to set email alerts
|

Dormancy, germination and seedling growth of two Kalaharian perennials of the genus Harpagophytum (Pedaliaceae)

Abstract: Dormancy and germination ecology of two Harpagophytum species (Pedaliaceae) from an open Acacia savanna in Botswana were investigated. The maintenance of dormancy is governed partly by the seed coat but mainly by the endosperm and the embryo itself, as demonstrated by removal of the endosperm. Dissemination of the seed from the fruit can be delayed for several years without affecting the viability of the embryo, due to very low respiration rates.Germination can be enhanced slightly by high temperatures under n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Out of these pretreatments tried, the seeds, which were pricked at the basal end and soaked in GA 3 overnight responded well. Ernst et al (1988) also reported the positive influence of GA 3 for seed germination of two Harpagophytum species. The soaked seeds were then surface-disinfected with 0.1 % HgCl 2 (m/v) for 3 min, followed by 3 washes in sterile distilled water, and transferred to half-strength MS basal medium (Murashige and Skoog 1962) containing 1 % (m/v) sucrose and 0.8 % (m/v) agar.…”
Section: Seeds From Dry Fruits and Primary Tubers Ofmentioning
confidence: 89%
See 1 more Smart Citation
“…Out of these pretreatments tried, the seeds, which were pricked at the basal end and soaked in GA 3 overnight responded well. Ernst et al (1988) also reported the positive influence of GA 3 for seed germination of two Harpagophytum species. The soaked seeds were then surface-disinfected with 0.1 % HgCl 2 (m/v) for 3 min, followed by 3 washes in sterile distilled water, and transferred to half-strength MS basal medium (Murashige and Skoog 1962) containing 1 % (m/v) sucrose and 0.8 % (m/v) agar.…”
Section: Seeds From Dry Fruits and Primary Tubers Ofmentioning
confidence: 89%
“…Due to its high medicinal importance (Van Haelen et al 1983), rural communities intensively harvest the species in the field. Furthermore, the seeds exhibit a high degree of dormancy (Ernst et al 1988) resulting in very poor seedling recruitment. Plant tissue culture techniques provide a suitable alternative method for mass propagation of this endangered species (Levieille and Wilson 2000, 2002, Afolayan and Adibola 2004.…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%
“…The flattened woody capsules, which give the plant its scientific and common names, bear two rows of curved arms studded with curved spines (Harpagophytum literally means grapple hook plant). The fruit is animal dispersed (Ernst et al, 1988), because it easily entangles itself in animal fur or wool, although it appears to be wind dispersed to some degree, as a breeze can carry a fruit for some distance from the parent plant. Seeds have a high degree of dormancy (Veenendaal, 1984;De Jong, 1985), which may be an adaptation to drought (Ernst et al, 1988).…”
Section: Ecology and Biologymentioning
confidence: 99%
“…The fruit is animal dispersed (Ernst et al, 1988), because it easily entangles itself in animal fur or wool, although it appears to be wind dispersed to some degree, as a breeze can carry a fruit for some distance from the parent plant. Seeds have a high degree of dormancy (Veenendaal, 1984;De Jong, 1985), which may be an adaptation to drought (Ernst et al, 1988). In addition, seeds are released slowly from the mature fruit.…”
Section: Ecology and Biologymentioning
confidence: 99%
See 1 more Smart Citation